2010
DOI: 10.1097/hp.0b013e3181c8f9ea
|View full text |Cite
|
Sign up to set email alerts
|

131i Biokinetics and Cytogenetic Dose Estimates in Ablation Treatment of Thyroid Carcinoma

Abstract: This study evaluated biokinetic behavior of radioiodine in the bodies of ten female adult patients, with well-differentiated thyroid cancer, treated with 131I post-near total thyroidectomy, for ablation of remnant thyroid. In vivo and in vitro bioassay analyses were performed from the first hour following radioiodine administration until minimum detection limits were reached. The retention of 131I in the body from day 1 to day 6 after the intake may be mathematically represented by an exponential decreasing cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
1
6
0
1
Order By: Relevance
“…[ 29 30 ] have also shown that MN frequency, as a biomarker of cancer risk, might not be reliable if it was investigated in lymphocytes which were affected by intensive cells proliferation as well as an apoptosis processes. Other reports[ 31 32 33 ] confirmed a statistically significant increase of cytogenetic damage detected after therapy although authors stressed strong influence of time between exposure and biomarkers monitoring. Our report is in agreement with all above observations.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…[ 29 30 ] have also shown that MN frequency, as a biomarker of cancer risk, might not be reliable if it was investigated in lymphocytes which were affected by intensive cells proliferation as well as an apoptosis processes. Other reports[ 31 32 33 ] confirmed a statistically significant increase of cytogenetic damage detected after therapy although authors stressed strong influence of time between exposure and biomarkers monitoring. Our report is in agreement with all above observations.…”
Section: Discussionmentioning
confidence: 94%
“…Nascimento et al . [ 31 ] evaluated the biokinetics of radioiodine in adult cancer patients from the 1 st hour following radioiodine administration until minimum detection limits were reached. Authors reported the exponential type of retention kinetics with two biological half-lives, 0.81 day from day 1 to day 6 after the I-131 intake, with increasing appearance later in urine, and after 2 weeks, the retention of iodine in the body followed an exponential decrease, with a half-life of about 15 days.…”
Section: Discussionmentioning
confidence: 99%
“…analytical assessments listed in Table 3 were made based on the exponential decay of two compartments and defined as instant or slow decay terms for the numerical analysis [15][16][17][18]20]. The most intricate model of Guiu-Souto et al [19] included ten compartments and assigned two feedback paths (from body fluid to stomach and liver to body fluid), whereas others either had no assigned feedback path or defined only one feedback path.…”
Section: Plos Onementioning
confidence: 99%
“…131 I therapy has been used for the ablation of well-differentiated thyroid carcinoma for more than six decades (21). This therapy is a rapid, stress-free, highly effective and simple for cats, dogs and people with hyperthyroidism (14,25).…”
Section: Introductionmentioning
confidence: 99%